Ritual dan Identitas Kolektif: Studi Antropologis atas Tradisi Perkawinan dalam Masyarakat Urban - Silvia, Kiranti (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
Marriage traditions are a cultural practice that not only represent social relations between individuals but also serve as an important medium in the formation and maintenance of a community's collective identity. Amidst rapid urbanization, there has been a shift in the values and meanings of marriage rituals, raising anthropological questions about how urban communities reinterpret these traditions. This study aims to examine the transformation of the meaning of marriage rituals in urban communities and their implications for the construction of collective identity. Using a qualitative approach with ethnographic methods, this study collected data through participant observation, in-depth interviews, and documentation of marriage ceremonies in several urban communities in Indonesia. The results show that despite modifications in form, symbols, and procedures, marriage rituals remain a space for the expression of communal identity. Adaptations to the urban context are demonstrated through the use of digital technology, simplification of the procession, and the adoption of modern symbols without eliminating deeply rooted traditional values. These changes demonstrate the creative dynamics of communities in maintaining cultural continuity in an adaptive manner. Collective identity is not formed through the uniformity of tradition, but through the negotiation of meaning between cultural heritage and the realities of urban life. The conclusion of this study confirms that marriage rituals remain a vital means of strengthening social solidarity and shared identity narratives, even amidst ongoing cultural transformation.